Ru(II)-Catalyzed C–H Activation and Alkyne Annulation Reaction of Phenyl Indandiones: Synthesis of Spirobi[indene]diones - Bora, Bidisha R.; Sultana, Sabera; Sarma, Bipul; Gogoi, Sanjib (Synthesis, 2022)
A Ru(II)-catalyzed synthesis of spirobi[indene]dione from phenyl indandione and alkyne is reported. This metal-catalyzed cyclization reaction proceeds through hydroxy group directed C(sp2)–H bond activation, keto–enol tautomerization and alkyne annulation pathways.
Keywords: annulation reaction; C–H activation; Ru catalysis; spirobi[indene]; phenyl indandione